Women and Expatriate Positions in Latin American Multinationals - Chaves Solano, Edgar E. (2009)
One of the most significant features of the global labor market in the last half of the 20th century has been the increasing labor force participation rate of women. It is evident from the existing research that women are not progressing to senior international management positions at comparable rates to their male counterparts. Previous research has estimated that only 3% of expatriate managers are women. It is argued that female international managers have to overcome overt and covert barriers in their home organizations before being developed for international assignments. The above-mentioned studies relate to developed countries. In the case of the Latin American corporations we have found no theoretical or empirical studies that project light on the subject of expatriate women. This paper aims at finding reasons and myths about assigning women as expatriates in the developed countries, in order to examine, in a later study, if these reasons are valid or not with regard to the expatriate women of Latin America corporations. These results will help managers to make better decisions when they have to fill a position abroad.